1998
DOI: 10.1046/j.1464-410x.1998.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of propiverine, atropine and oxybutynin on bladder instability in rats with infravesical outlet obstruction

Abstract: Objective To compare the inhibitory eCects of propiveratropine increased the RV only in normal rats (P<0.01) and oxybutynin had no significant eCect on ine HCl (BUP-4) with those of atropine and oxybutynin on the detrusor instability induced by partial obstruc-RV. Increases in compliance after the administration of each drug were significant only in obstructed rats tion of the bladder neck of female rats. Materials and methods Partial obstruction was created (P<0.01) and were markedly higher after oxybutynin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
1
4
2
1
Order By: Relevance
“…In addition, in this last experimental condition, oxybutynin did not modify the frequency and amplitude of the non-voiding contractions. These findings are in agreement with the lack of activity shown by tolterodine in the same model [31], whereas Kwak and Lee [14] reported a significant decrease of frequency and amplitude of the non voiding contractions in anesthetized rats after intraarterial administration of 1 mg/kg oxybutynin.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, in this last experimental condition, oxybutynin did not modify the frequency and amplitude of the non-voiding contractions. These findings are in agreement with the lack of activity shown by tolterodine in the same model [31], whereas Kwak and Lee [14] reported a significant decrease of frequency and amplitude of the non voiding contractions in anesthetized rats after intraarterial administration of 1 mg/kg oxybutynin.…”
Section: Discussionsupporting
confidence: 87%
“…Outflow obstruction may be associated with changes in the cholinergic function of the bladder associated with an increase of atropine-resistance. Again, the bladder instability seen in obstructed rats seems to be particularly related to the atropine-resistant contraction component, where ATP and prostaglandins play an important role [14]. However, we found that oxybutynin did not increase BVC either in rats under infusion of the bladder with suramin, or in obstructed rats.…”
Section: Discussioncontrasting
confidence: 51%
“…We have observed that after 4 weeks of partial obstruction, bladder weigh in the animals of G2 group (obstructed) was 2.5 times higher than in G1 group (control). Other authors (13,15,17) observed a significant increase in rabbits' bladder weight after 4 weeks of partial obstruction. This fact could occur due to the presence of hypertrophy and hyperplasia of vesical wall (20).…”
Section: Discussionmentioning
confidence: 86%
“…Thus, there are different experimental models described for partial bladder outlet obstruction using guinea pig (3), rabbit (4,5), cat (6), dog (7), pig (8), and rat (9). The models described aimed to characterize bladder functional alterations caused by partial obstruction, but few works take into account the development of uninhib-ited detrusor contractions (9)(10)(11)(12)(13). This obstruction was performed in most cases constricting the urethrovesical junction with a suture tie (14,15), a polyethylene tube (16), or a silicone strip (17).…”
Section: Introductionmentioning
confidence: 99%
“…It has a dual mode of action which includes both anticholinergic and calcium antagonistic properties. In rats with detrusor instability induced artificially by outflow obstruction, this agent appears to be as effective as oxybutynin at suppressing spontaneous detrusor activity [38]. Direct comparative trials in humans with oxybutynin and/or tolterodine would be of interest.…”
Section: Pharmacotherapymentioning
confidence: 99%